‘Morning Sen’: Interaction, Habitus and the Importance of Uniform as Identity in Aviation College - Sari, Nanik Rianandita (Komunitas, 2017)
Uniform is a brand of identity. STTKD is a semi military aviation college which has a unique interaction as habitus among them and academic staff. This study examines of STTKD’s cadets experiences by exploring how his uniform become his habitus and influenced his social and academic integration into higher education. This research found that by using Uniform, cadets provides professional and discipline, and to be a responsible individual who will demand of themselves, high standards of achievement. There are some unique interaction and habitus that found in this research, like: ‘morning sen’ as daily interaction between cadet and even academic staff, morning parade, and sweeping that every junior need to attend. Of all these interactions make cadets respect others.